SAS programming in the pharmaceutical industry - Shostak, Jack (SAS Institute, 2005)
At last! A real-world reference guide for clinical trial SAS programming, packed with solutions that programmers can apply to their day-to-day problems. Discover key techniques and tools available within Base SAS (including the macro language and PROC SQL), SAS/GRAPH, and SAS/STAT that can be used to resolve many common issues in working with clinical trial data. Organized to reflect the statistical programmer's work flow, this user-friendly text begins with an introduction to the working environment, then presents chapters on importing and massaging data into analysis data sets, producing clinical trial output, and exporting data. Valuable plug-and-play programming examples are provided throughout. Whether you're a novice seeking an introduction to SAS programming for the pharmaceutical industry or a junior-level programmer exploring new approaches to problem solving, you'll find a wealth of practical suggestions to help you sharpen your skills.
Includes bibliographical references and index
Keywords: SAS (Computer file); Pharmaceutical technology -- Data processing; Pharmaceutical industry -- Data processing; Techniques pharmaceutiques; Informatique; Industrie pharmaceutique; Informatique; MEDICAL; Drug Guides; MEDICAL; Pharmacology; MEDICAL; Pharmacy; MEDICAL; Nursing; Pharmacology; Pharmaceutical technology; Data processing; Pharmaceutical industry; Data processing